Antibiotic Resistance of Shigella Species in Iran - A.Mehr-Movahed; J. Nikkhah (Tehran University of Medical Sciences, 1987)
Antibiotic resistance in Shigella species has been showing a rising trend all over the world. This study was performed to discover the state of antibiotic resistance of Shigella species with regards to six common antibiotics in use in Iran.